Analysis of the possibilities of using a ventilation system decentralized in educational buildings - Amanowicz , Łukasz; Ratajczak , Katarzyna; Szczechowiak , Edward (Instal, 2019)
occur. In turn, the possibility of air filtration, heat recovery and adaptation of the ventilation air flow to the current needs (in the function of room load of carbon dioxide, steam or depending on the number of people) allows to improve air quality and climate comfort. In addition, devices of this type can be easily used in existing buildings, because they do not require the installation of an air distribution system, which makes us think about the timeliness and legitimacy of the existing legal requirements.
Keywords: decentralized ventilation; investigations of air intake and exhaust device; heat recoveryt; education buildings; indoor air quality